Mini dental implants retaining mandibular overdentures: a dental practice-based retrospective analysis - Schwindling, Franz Sebastian; Schwindling, Franz-Peter (Journal of prosthodontic research, 2016)
Purpose The purpose of this study was to assess the survival of mini dental implants (MDI) and to measure prosthetic maintenance needs in a dental practice-based setting. Methods Patients with mandibular removable dentures were provided with MDI to improve denture retention. Complications and maintenance were analyzed by use of patient records and evaluated with Kaplan-Meier curves and the log rank test at a significance level of 0.05. Results Ninety-nine MDI were placed in 25 patients (mean age: 72 years). Two MDI fractured during placement and eight implants failed during the first weeks. No more implants were lost for up to seven years, resulting in 92% survival. Implant survival differed significantly depending on whether the maxilla was provided with complete dentures (94.9%) or with partial dentures (81%). All prostheses were in use at the time of data extraction. Denture base fractures were observed in six cases, an incidence of fractures of 24%. Some minor intervention was necessary: one resin tooth fractured, retention rings were changed in five cases, and repeated relining was required for 16% of the dentures. Conclusions After mid-term observation, survival of MDI was good. However, the incidence of denture base fractures and of minor prosthetic complications should not be under-estimated.